2017
DOI: 10.1642/auk-16-216.1
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of counting songbirds using unmanned aerial vehicles

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 50 publications
0
59
0
Order By: Relevance
“…Also, deployment to inaccessible areas with unmanned aerial vehicles is feasible (Wilson et al. ), and installation on cars can also be envisaged (Jeliazkov et al. ).…”
Section: Practicalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, deployment to inaccessible areas with unmanned aerial vehicles is feasible (Wilson et al. ), and installation on cars can also be envisaged (Jeliazkov et al. ).…”
Section: Practicalitymentioning
confidence: 99%
“…Furthermore, Prevost (2016) showed that sound recorders were amenable to installation on hot air balloons, due to their low size and weight. Also, deployment to inaccessible areas with unmanned aerial vehicles is feasible (Wilson et al 2017), and installation on cars can also be envisaged (Jeliazkov et al 2016). In the future, large geographical scales could also be sampled using autonomous wireless recorder networks that collect and transmit data wirelessly (Collins et al 2006).…”
Section: Practicalitymentioning
confidence: 99%
“…In addition, combustion engines present risks associated with engine ignition. Multiple studies considered electric UASs to be an excellent tool for approaching and surveying birds because of their low noise [57][58][59][60][61]. Table 1 shows a comparison of spaceborne, manned aerial, and UAS surveys of animals, including the platforms used, sensors, image resolution, data cost, coverage, availability, surveyed species, animal detection methods, pixel number of surveyed species in the imagery, and detection accuracy.…”
Section: Sensorsmentioning
confidence: 99%
“…Many bird species are highly suited to RPA‐facilitated population monitoring. RPA have been used to assess the breeding status of the canopy‐breeding hooded crow Corvus cornix (Weissensteiner, Poelstra, & Wolf, ) and to take a census of multispecies assemblages of songbirds (Wilson, Barr, & Zagorski, ). They have also been a useful tool in collecting valuable datasets of species which congregate and/or those that frequent known sites to breed.…”
Section: Introductionmentioning
confidence: 99%